Hydraulic Calculation of the Movement of Sediments in the River Flow by the Length of the Flow - Arifdjanov, A.; Iminov , I. (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
As you know, it is also important to study the order of movement of blurred sediments in open ones, as well as to analyze the process of deposition of suspended sediments during its analysis. From field studies as well as from scientific and theoretical conclusions, the deposition of turbid particles in the stream along the length of the stream will also depend on changes in the flow rate and flow. This article will consider the hydraulic calculation of river sediments by the length of the flow.